Generation of new glutinous rice by CRISPR/Cas9‐targeted mutagenesis of the Waxy gene in elite rice varieties - Zhang, Jinshan; Zhang, Hui; Botella, José Ramón; Zhu, Jian‐Kang (Journal of integrative plant biology, 2018)
Summary In rice, amylose content (AC) is controlled by a single dominant Waxy gene. We used Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR‐associated 9 (Cas9) to introduce a loss‐of‐function mutation into the Waxy gene in two widely cultivated elite japonica varieties. Our results show that mutations in the Waxy gene reduce AC and convert the rice into glutinous ones without affecting other desirable agronomic traits, offering an effective and easy strategy to improve glutinosity in elite varieties. Importantly, we successfully removed the transgenes from the progeny. Our study provides an example of generating improved crops with potential for commercialization, by editing a gene of interest directly in elite crop varieties. In this study, we reported generation of new glutinous rice with potential for commercialization by editing Waxy gene in elite crop varieties.